2018
DOI: 10.1021/acs.molpharmaceut.8b00697
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Functional Characterization of Drug Transporters in Brain Microvascular Endothelial Cells Derived from Human Induced Pluripotent Stem Cells

Abstract: Brain microvascular endothelial cells derived from human induced pluripotent stem cells (hiPS-BMECs) have been proposed as a new blood–brain barrier model, but their transport function has not been fully clarified. Therefore, in this study, we investigated the gene expression and function of transporters in hiPS-BMECs by means of quantitative reverse transcription-PCR, in vitro transcellular transport studies, and uptake experiments. mRNAs encoding ABC and SLC transporters, such as BCRP, MCT1, CAT1, and GLAST,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 33 publications
5
55
0
Order By: Relevance
“…It may be that the transporter was not sufficiently expressed. For example in a recent study, MATE1 mRNA was below the limit of quantification in hCMEC/D3 cells (Kurosawa et al 2018), but had been detected in an earlier study albeit at low levels(Shimomura et al 2013). Other considerations are that the inhibitor may need to reach a therapeutic concentration within the cell to elicit a response as has been observed with MATE1 inhibitors (Tsuda et al 2009), the substrate and the inhibitor may bind to different binding sites, the non-specificity of the inhibitor, and that amisulpride interacts with both influx (OCT) and efflux (PMAT) transporters(Wittwer et al 2013)(Wu et al 2015)(Bourdet 2005).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…It may be that the transporter was not sufficiently expressed. For example in a recent study, MATE1 mRNA was below the limit of quantification in hCMEC/D3 cells (Kurosawa et al 2018), but had been detected in an earlier study albeit at low levels(Shimomura et al 2013). Other considerations are that the inhibitor may need to reach a therapeutic concentration within the cell to elicit a response as has been observed with MATE1 inhibitors (Tsuda et al 2009), the substrate and the inhibitor may bind to different binding sites, the non-specificity of the inhibitor, and that amisulpride interacts with both influx (OCT) and efflux (PMAT) transporters(Wittwer et al 2013)(Wu et al 2015)(Bourdet 2005).…”
Section: Discussionmentioning
confidence: 83%
“…However, in vitro inhibitor studies with lopinavir, suggest that amisulpride could be effluxed by PMAT. This transporter is expressed on brain capillaries (Figures 7, S19B, S19C and S28) (Shimomura et al 2013)(Hiasa et al 2006)(Wu et al 2015)(Kurosawa et al 2018). PMAT mRNA and protein has also been identified on the luminal and abluminal membrane of human, mouse and rat brain endothelial cells(Wu et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…relevant for ABC transporter profiles, since it is known that the transporter ABCB1 can be upregulated during epilepsy [22]. The comparison of the expression of ABC transporters in hCMEC/D3 under standard conditions with mRNA and proteomics data from isolated capillaries showed that only ABCB1, ABCG2 and ABCC4 were detected at the protein level in human brain capillaries, whereas on the mRNA level ABCB1, ABCC5, ABCG2, ABCC1 and ABCC4 could be found in this expression order (ABCC2 and ABCC3 were not measured on the mRNA level in the brain capillaries [23,40,45]). Analysis of hCMEC/D3 samples showed that all tested ABC transporters of this work were also found in previous publications, but partly in different order (mRNA: ABCB1, ABCC3, ABCC1, ABCC4, ABCC5 and very little ABCC2, [48]; protein: ABCB1, ABCG2, ABCC1, ABCC4 (ABCC2, 3 and 5 under detection limit); [35].…”
Section: Discussionmentioning
confidence: 98%
“…Early iPSC-derived BBB models highlighted the ability of iBMECs to correlate well with in vivo drug permeability using transwell systems [12,71] and subsequent studies have expanded permeability testing to microfluidic platforms under fluid flow that more closely mimic in vivo conditions [19,31,64]. Importantly, iBMECs express many of the necessary efflux pumps and transporters [18,31,39] and have successfully been used to investigate general drug transport as well as specific transporter-drug interactions such as LAT1 with gabapentin [72]. Furthermore, iBMECs can be co-cultured with other cells of the NVU that can potentially alter drug permeabilities through changes in barrier properties or transporter expression [24], and hence should be considered when designing drug screening platforms.…”
Section: Drug Transport and Deliverymentioning
confidence: 99%
“…Despite iBMECs expressing many of the necessary solute channel and ATP-binding cassette transporters [18,38,39], expression levels of some of these transporters fall below in vivo values [31,72,78], suggesting that further maturation of iBMECs or modification to culturing conditions may be required to match in vivo levels. The current explosion of single-cell RNA-sequencing will likely help delineate some of the in vitro versus in vivo differences and has recently uncovered the vast and previously underappreciated heterogeneity in brain microvasculature [79], which has not been addressed in iPSC-derived BBB models.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%